2011
DOI: 10.1016/j.nut.2010.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Associations between glutathione peroxidase-1 Pro198Leu polymorphism, selenium status, and DNA damage levels in obese women after consumption of Brazil nuts

Abstract: Consumption of one unit of Brazil nuts daily effectively increases Se status and increases GPx activity in obese women, regardless of GPx1 Pro198Leu polymorphism. However, the evaluated biomarkers showed distinct results in response to the supplementation when the polymorphism was considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 43 publications
5
57
1
10
Order By: Relevance
“…This finding agrees with the findings observed by Hu and Diamond [40], by Jablonska et al [38], and by Cominetti et al [41], which presumed that Leu allele is less responsive to the increasing of Se intake.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding agrees with the findings observed by Hu and Diamond [40], by Jablonska et al [38], and by Cominetti et al [41], which presumed that Leu allele is less responsive to the increasing of Se intake.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we determined the genotype and allele frequencies in a Brazilian population, and the results regarding the heterozygote allele frequency were different from another study carried out in our country [41]. On the other hand, the homozygous variant allele frequency was quite similar to other studies [19,20,21,38,41,42,43] and higher than that found in Asiatic populations [44,45,46]. It is important to highlight that these findings should not be generalized to other populations since different ethnic attitudes regarding lifestyle may influence the results.…”
Section: Discussionmentioning
confidence: 63%
“…The supplementation with Brazil nuts has been found to be effective in increasing concentrations of Se biomarkers in several studies. However, only three biomarkers were commonly used (GPx1 activity, Plasma Se and Erythrocyte Se) and only one genetic variation in GPX1 gene, rs1050450, is mostly considered (COMINETTI et al, 2011THOMSON et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…É o caso, por exemplo, de alguns estudos que mostram uma atividade reduzida da enzima GPx, durante a baixa concentração de Se, ou aumentada com a suplementação (83,93,101,102,103,104,105,106,107,108,109).…”
Section: -Funções Do Seunclassified